A new mixed-integer programming model for joint inventory-transportation problem in a social responsible supply chain. (1st January 2013) - Razmi, J.; Amini, A.; Pishvaee, M.S.
The role of corporate social responsibility (CSR) in supply chain management is an interesting subject that has attracted significant efforts of researchers and practitioners in recent years. This paper addresses the joint inventory-transportation problem in a three-echelon social responsible supply chain. A new bi-objective mixed-integer mathematical programming model is developed that its first objective function aims to minimise the total costs including transportation costs and inventory holding and shortage costs, while the second one maximises the social responsibility of the supply chain. To form the second objective function three credible CSR criteria are selected from the CSR measurement frameworks existed in the relevant literature. To show the performance and applicably of the proposed model an illustrative example is used. The illustrative example is solved by GAMS optimisation software and the corresponding results as well as some managerial implications are reported in the paper.